SELF-EFFICIENCY OF BIOLOGY EDUCATION STUDENTS CLASS OF 2018 IN PREPARING THESIS: EFIKASI DIRI MAHASISWA PENDIDIKAN BIOLOGI ANGKATAN 2018 DALAM MENYUSUN SKRIPSI - Nurlia (SOSIOEDUKASI, 2023)
This study aims to determine the level of self-efficacy of final semester students who are preparing a thesis. This type of research is descriptive quantitative. This research was carried out in September 2022. The subjects of this research were all 17 students of the Biology Education study program at the Universitas Muhammadiyah Luwuk class of 2018 as many as 17 people. Collecting data using a closed questionnaire technique with a Likert scale consisting of four answer choices, namely strongly agree, agree, disagree and strongly disagree. Questionnaires were given to students via google forms as many as 35 statements out of 10 indicators. The data analysis technique used in this research is descriptive categorization by grouping data, tabulating data, presenting data and calculating research data. Categorization of self-efficacy consists of very high, high, medium, low and very low. Based on the results of data analysis, it was found that there were 8 students (47.1%) who had self-efficacy in the very high category, 8 students (47.1%) were in the high category, 1 student (5.8%) was in the medium category. This means that students of Biology Education study program at the Universitas Muhammadiyah Luwuk batch 2018 who are currently compiling their thesis mostly have self-efficacy in the high and very high categories.